2005
DOI: 10.1590/s0100-879x2005000700001
|View full text |Cite
|
Sign up to set email alerts
|

What about Th1/Th2 in cutaneous leishmaniasis vaccine discovery?

Abstract: The T helper cell type 1 (Th1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 36 publications
1
44
0
Order By: Relevance
“…Several candidate vaccine molecules have already been evaluated in the mice model for leishmaniasis (8 -14). Treatment and vaccination that control the disease in susceptible mice invariably promote Th1 responses over Th2 responses (15)(16)(17)(18). However, this may or may not hold true for other models of leishmaniasis.…”
Section: Ubiquitin Conjugation Of Open Reading Frame F Dna Vaccine Lementioning
confidence: 99%
“…Several candidate vaccine molecules have already been evaluated in the mice model for leishmaniasis (8 -14). Treatment and vaccination that control the disease in susceptible mice invariably promote Th1 responses over Th2 responses (15)(16)(17)(18). However, this may or may not hold true for other models of leishmaniasis.…”
Section: Ubiquitin Conjugation Of Open Reading Frame F Dna Vaccine Lementioning
confidence: 99%
“…However, other studies suggest that this association is not consistently observed [17,18,19]. The induction of polarized T cell responses, and their association with infection-induced pathology or disease-protective mechanisms has led to the development of novel vaccines and immunotherapeutics [20,21].…”
Section: Discusssionmentioning
confidence: 99%
“…The concept of Th1/Th2 immune response involvement in disease pathology has recently been re-evaluated in the context of vaccine development and immunologic intervention [20,21]. In Leishmaniasis, Th1 responses are protective and th2 response are disease promoting, which is opposite to the P. gingivalis, paradigm.…”
Section: Discusssionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far the leishmanin (Montenegro) skin test is the most informative and practical immunological surrogate marker used in clinical trials [21]. With a complementary rationale Campos-Neto [22] has shown that disease-associated Th2 antigens of Leishmania can be protective if a Th1 response to them is generated before infection. Moreover, the immune response to a given antigen (e.g., LACK) can be protective (Th1) or exacerbating (Th2), depending on the way the antigen is introduced [23] or on the genetic background of the mouse.…”
Section: Mechanisms Of Protective Immunitymentioning
confidence: 99%